2010
DOI: 10.1111/j.1461-0248.2009.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric CO2 enrichment facilitates cation release from soil

Abstract: Atmospheric CO(2) enrichment generally stimulates plant photosynthesis and nutrient uptake, modifying the local and global cycling of bioactive elements. Although nutrient cations affect the long-term productivity and carbon balance of terrestrial ecosystems, little is known about the effect of CO(2) enrichment on cation availability in soil. In this study, we present evidence for a novel mechanism of CO(2)-enhancement of cation release from soil in rice agricultural systems. Elevated CO(2) increased organic C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
121
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 40 publications
3
121
3
Order By: Relevance
“…5A). Because aspects of global change also impact ecosystem Mn fluxes, bioavailability in soils (43,44), plant uptake, and foliar litter concentrations (45), the tight coupling we demonstrate between Mn cycling and litter decomposition suggests that further research on regulators of ecosystem Mn fluxes is warranted.…”
Section: Discussionmentioning
confidence: 95%
“…5A). Because aspects of global change also impact ecosystem Mn fluxes, bioavailability in soils (43,44), plant uptake, and foliar litter concentrations (45), the tight coupling we demonstrate between Mn cycling and litter decomposition suggests that further research on regulators of ecosystem Mn fluxes is warranted.…”
Section: Discussionmentioning
confidence: 95%
“…Base cations (i.e., 43 exchangeable Ca, Mg, K, Na) are the predominant exchangeable cations in the 44 calcareous soils (Zhang et al, 2013). They are essential for soil buffering capacity 45 particularly in soils affected by atmospheric acid deposition (Lieb et al, 2011), serve 46 as good indicators of soil fertility (Zhang et al, 2013), and are critical nutrients for 47 both plant and microbial metabolism (Cheng et al, 2010). For instance, Ca regulates 48 plant cell signaling, cell division, and carbohydrate metabolism (McLaughlin and 49 Wimmer, 1999), and Mg is important for photosynthesis and energy storage (Lucas et 50 al., 2011).…”
mentioning
confidence: 99%
“…The availability of base cations varies with edaphic properties, such 57 as soil pH (Katou, 2002), organic matter fractions (Oorts et al, 2003) and soil particle 58 sizes (Beldin et al, 2007). Prolonged N inputs generally causes soil acidification and 59 subsequent losses of soil cations (McLaughlin and Wimmer, 1999;Cheng et al, 2010), 60 and micronutrient availability may increase under soil acidification (Malhi et al, 1998) 61 causing toxicity to both plants and soil microorganisms in extreme cases (Bowman et Soil aggregate structure predominantly controls SOM dynamics (Six et al, 2004) 69 and microbial activities (Dorodnikov et al, 2009), and soil aggregate stability can 70 serve as an indicator for grassland ecosystem health (Reinhart et al, 2015). In 71 comparison with macroaggregates, microaggregates provide preferential sites for soil 72 C stabilization (Wang et al, 2015b) and the SOM herein is more microbial-processed 73 as evidenced by natural abundance stable 13 C values (Gunina and Kuzyakov, 2014; 74 Wang et al, 2015b).…”
mentioning
confidence: 99%
“…This broad hypothesis has been extensively tested over the past two decades for CO 2 but less so with O 3 [4,10,12,13,14,15,16]. Though C availability to microbes has been commonly reported to increase under elevated CO 2 [5,17,18] and to decrease under elevated O 3 [6,13,19], results of soil microbial responses to elevated CO 2 and O 3 have been inconsistent [6,11,20,21]. In a meta-analysis study, de Graaff et al (2006) found that elevated CO 2 increased microbial biomass C and microbial respiration by 7.7% and 17.1%, respectively, across 40 studies that mainly included herbaceous species.…”
Section: Introductionmentioning
confidence: 99%
“…Soil extractable C and N. The concentration of organic C in non-fumigated soil extracts was used to represent soil extractable C. The extractable inorganic N referred to the sum of NH 4 + -N and NO 3 2 -N in non-fumigated soil extracts.…”
mentioning
confidence: 99%